A CORRELATION BETWEEN STUDENTS’ MASTERY OF FUNCTIONAL GRAMMAR AND THEIR ACHIEVEMENT IN WRITING RECOUNT: A STUDY AT AN ISLAMIC BOARDING SCHOOL - Hikmah Pravitasari; Royhan Kamal (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2023)
This study explores the correlation between students' mastery of functional grammar and their achievement in writing recount texts, conducted within the context of an Islamic boarding school. The research aims to address two main questions: (1) How do male and female students perform in grammar learning and writing skills and (2) Is there a correlation between the mastery of functional grammar and students’ writing skills in junior high school. The study collected the data from eighth-grade students and categorized the results according to gender. The findings demonstrated that male and female students performed slightly differently in functional grammar tests and writing tests. The lowest functional grammar exam score for male students was 58, while it was 52 for female students. In contrast, the top scores for both genders were 97. In the writing assessment, similar differences were found, with male students scoring as low as 60 and female students scoring as low as 48. A group of both male and female students obtained the highest maximum score of 100. This research also investigates the relationship between students' functional grammar mastery and their ability to write factual recount texts. The estimated r-count value of 0.9487 was found to be significantly higher than the r-table value of 0.3550, r-count (0.9487) > r-table (03550) using the Pearson product-moment correlation and a significance level of 0.05, showing a significant positive correlation. Hence, it can be concluded that the implementation of functional grammar has a significant influence in developing students' writing skills on factual recount text with the aim that they are not only able to arrange words into a paragraph, but also able to convey the ideas and meanings they express in their writing.